BIOLOGI REPRODUKSI IKAN TONGKOL (Euthynnus affinis) YANG DIDARATKAN DI PANGKALAN PENDARATAN IKAN TANJUNG LUAR KABUPATEN LOMBOK TIMUR - Pahmi Husain; Karnan Karnan; DIdik Santoso (Jurnal Inovasi Pendidikan dan Sains, 2021)
The eastern little tuna is one of a pelagic fish that has an economic important value and mostly landed at Fish Base Landing (PPI) Tanjung Luar. The needs of eastern little tuna are very affordable and sold economically in the markets, which causes a highly catching intensity by the fishermen regardless the catching season, so that many eastern little tuna which caught when they were in gonads matured and spawn session. The purpose of this study was to describe reproduction aspects comprises of gonads maturity stages, gonadosomatic index and fecundity. This research was taken on May till June 2018 from Fish Base Landing in Tanjung Luar. The total samples observed were 120 female fishes which collected from the fish base landing. The sample determination technique in this study was quota sampling. Gonad maturity stages were observed by morphological observation then the gonadosomatic index were measured. Fecundity ware treated on 36 samples at V and VI stages (gonads matured) to be measured by using gravimetric method. The result of this study revealed that gonads maturity of the female eastern little tuna was dominated by the fourth stage (51,67%), and then followed by the fifth stage (36,67%), the third stage (23,33%), the sixth stage (8,33%) the second stage (8,33%) and the first stage (6,62%). From those gonad maturity percentages showed that the eastern little tuna was not in the gonads matured session. The value of gonadosomatic index for the female eastern little tuna were about 0,0116% up to 0,0258%. Meanwhile the fecundity range between 192.246 ova until 601.497 ova on fish with the length between 415 mm until 640 mm.